Relationship between High Fat Diet and Risk of Hyperlipidaemia in Primary School Children in Surabaya - Vincentia Maria Iriane; Yuswanto Setyawan (POLTEKKES KEMENKES PONTIANAK, 2025)
The prevalence of hyperlipidaemia in children in Indonesia is 84.7%, which is very high. Although the health consequences of overweight in children are still poorly studied compared to adults, overweight in children has been consistently reported as a major risk factor for future metabolic conditions, such as type 2 diabetes mellitus, metabolic syndrome, cardiovascular disease, and some cancers. This study focuses specifically on primary school children only and the research location is in Surabaya. The purpose of this study was to analyse the relationship between the level of fat consumption and blood lipid levels in primary school children. This research method is cross-sectional. In this study, data were collected using the Modified Food Frequency Questionnaire (FFQ) and measurement of total cholesterol, LDL, HDL, and triglyceride levels through blood samples and analysed using chi square test and spearman correlation using SPSS Software. The results found that elementary school children who rarely consume high-fibre foods have a 6x greater risk of hyperlipidemia than in the category of frequent consumption of high-fibre foods. Suggestions for future research are expected to analyse hyperlipidemia in children and be associated with gender in elementary school students in order to know more in-depth differences.